Effect of yoga practices on Hs-CRP in Indian railway engine drivers of metropolis - Shete, Sanjay Uddhav; Kulkarni, Dattatraya Devrao; Thakur, Ghanshyam (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Objectives: To examine the effect of yoga training on high sensitivity C reactive protein (hs-CRP) and lipid profile levels in railway engine drivers working in metropolis. Methods: Male drivers of Indian railways, age ranged from 30 to 42 yrs with no known medical disorders, were randomized to yoga group (n=16) and control group (n=16). At the baseline and after completion of one month yoga training both the groups were assessed for hs-CRP and lipid profile levels. The yoga group practiced in a set of yoga techniques for 1 hr. daily in the morning along with daily routine work, while control group engaged in daily routine work only. Results: Statistically significant reduction (p<0.01) was evident in both hs-CRP and serum total cholesterol. Conclusion: Yoga based lifestyle modifications could contribute to prevention of coronary artery disease.Â 